RANCANGAN HANDOUT BIOLOGI PADA MATERI BAKTERI UNTUK SMA KELAS X - Daniatul Isra; Zulfarina Zulfarina; Yuslim Fauziah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The explanation on bacterial topic in the main teaching materials used by the teacher is general and is not explained in detail, the examples given are universal and not contextual which have an impact on low student learning achievements. Thus, teachers are required to be able to create a learning process that is more innovative, factual, and contextual. Handout can be desiagning for Teaching materials on bacterial topic. This study aims to determine the potential of biology handout design on bacterial topic for Senior High School Grade X. This research was conducted at FKIP, Riau University in December 2020-March 2021. This study used the ADDIE model, which is analysis and design stages. The results showed that the analysis phase, by analyzing the curriculum, syllabus, KD, and the material in accordance with the results of the study. The design stage is designing learning tools in the form of a syllabus and lesson plans, and designing a handout consisting of a cover, foreword, contents, study instructions, (KI, KD, and IPK), introduction, elaboration of subject matter, evaluation, and reference sources. The conclusion is the biology handouts design on KD 3.5 and KD 4.5 specifically for bacterial topic can be used as handout teaching materials for Senior High School student Grade X.Key Words: Handout. Bacteria